2005
DOI: 10.5650/jos.54.355
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Enzymatic Extraction of Oil from Mandarin Peels

Abstract: Citrus fruits represent the third major fruit in India, next to Mango and Banana. Citrus fruits comprise about 10% of total fruits produced in India (4.57 million tones out of 44.04 million tones) (1). It occupies about thirteen percent of total area under fruit cultivation (0.48 million hectare out of 3.72 million hectare). India produces about five million tones of Citrus fruit cultivated over 0.5 million-hectare area. The production of Citrus fruit in India is about seventy four percent of the world citrus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…The use of enzymatic hydrolysis is also beneficial in the case of essential oils obtained from the peel of citrus fruits such as mandarins (15%) (Mishra et al . ) and bergamots (Figoli et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of enzymatic hydrolysis is also beneficial in the case of essential oils obtained from the peel of citrus fruits such as mandarins (15%) (Mishra et al . ) and bergamots (Figoli et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…A higher yield of essential oil following enzymatic pretreatment was also observed in the case of other raw materials, such as cumin (18.5-22.2%) (Sowbhagya et al 2011), garlic (twofold increase) (Sowbhagya et al 2009), celery seeds (22.2-27.7%) (Sowbhagya et al 2010) and forsythia fruit (Fructus forsythia) (45.33%) (Jiao et al 2012). The use of enzymatic hydrolysis is also beneficial in the case of essential oils obtained from the peel of citrus fruits such as mandarins (15%) (Mishra et al 2005) and bergamots (Figoli et al 2006). It has also been found that the use of Citrozym CEO containing hemicellulases, pectinases and polygalacturonase for pretreatment of citrus peel reduces the viscosity of the emulsion and assists in breaking it up to recover essential oil from the aqueous phase, which results in increased yield of the oil and reduced fresh water consumption, without affecting the quality of the oil (Coll et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Mishra et al . () used enzymes to improve the extraction of essential oils from the flavedo of mandarin orange peels. Their proposed enzymatic process involved Xylanases enzyme pre‐treatment (at concentrations of 0.1–0.3%), followed by conventional hydrodistillation and cold press.…”
Section: Extraction Techniques For the Valorisation Of Orange Peelmentioning
confidence: 99%
“…Many types of spices and herbs are known to possess anti-insect activity especially in the form of essential oils [4][5][6] . Toxic effects of many monoterpenes from essential oils like d-limonene, linalool and terpeneol were observed in several insects damaging stored products 7) .…”
Section: Introductionmentioning
confidence: 99%